The constitutional right to freedom of association: a current look at its content and scope - Quiñones Infante, Sergio (2019)
This paper analyze the normative and jurisprudential development of the constitutional right to freedom of association. In the first place, it establishes the constitutional, conceptual and international frame of reference. Then, it seeks to clarify the conceptual difference between the notions of “capacity” and “legitimacy” to negotiate and evaluate the impact that this has on collective bargaining. Likewise, the legal possibility is analyzed that the parties delimit subjectively and temporarily the scope of a collective agreement and that they can freely set the bargaining levels. Finally, it is stated that union benefits, such as the union leave, are also an integral part of the constitutionally protected content of freedom of association.